Viral Isolation In Hospitalized Patients With Lower Respiratory Infections, In Children Under 5 Years In Hospital De Emergencias Pediatricas. Lima - Peru, 2014 - Mezarina-Esquivel, Hugo (2019)
Objective. Determine the viral etiology and epidemiological clinical features of hospitalized children with acute lower respiratory infection in Pediatric Emergency Hospital. Materials and methods. Observational study in 171 patients under 5 years of age hospitalized during 2014, with acute lower respiratory infection and who underwent the direct immunofluorescence test samples nasal or throat.